Diagnosis of alpha-1 antitrypsin deficiency: a population-based study - Barrecheguren M (International Journal of COPD, 2016)
Miriam Barrecheguren,1,2 Mónica Monteagudo,3 Pere Simonet,3–5 Carl Llor,6 Esther Rodriguez,1,7 Jaume Ferrer,1,2,7 Cristina Esquinas,1 Marc Miravitlles1,2,7 1Department of Pneumology, Vall d´Hebron University Hospital, 2Medicine Department, Autonomous University of Barcelona (UAB), 3IDIAP Jordi Gol, 4Departament Ciències Clíniques, Universitat de Barcelona, Barcelona, 5Primary Care Centre Viladecans-2, Viladecans, 6Primary Care Centre Via Roma, Barcelona, 7CIBER of Respiratory Diseases (CIBERES), Spain Introduction: Alpha-1 antitrypsin deficiency (AATD) remains an underdiagnosed condition despite initiatives developed to increase awareness. The objective was to describe the current situation of the diagnosis of AATD in primary care (PC) in Catalonia, Spain.Methods: We performed a population-based study with data from the Information System for Development in Research in Primary Care, a population database that contains information of 5.8 million inhabitants (80% of the population of Catalonia). We collected the number of alpha-1 antitrypsin (AAT) determinations performed in the PC in two periods (2007–2008 and 2010–2011) and described the characteristics of the individuals tested.Results: A total of 12,409 AAT determinations were performed (5,559 in 2007–2008 and 6,850 in 2010–2011), with 10.7% of them in children. As a possible indication for AAT determination, 28.9% adults and 29.4% children had a previous diagnosis of a disease related to AATD; transaminase levels were above normal in 17.7% of children and 47.1% of adults. In total, 663 (5.3%) individuals had intermediate AATD (50–100 mg/dL), 24 (0.2%) individuals had a severe deficiency (<50 mg/dL), with a prevalence of 0.19 cases of severe deficiency per 100 determinations. Nine (41%) of the adults with severe deficiency had a previous diagnosis of COPD/emphysema, and four (16.7%) were diagnosed with COPD within 6 months.Conclusion: The number of AAT determinations in the PC is low in relation to the prevalence of COPD but increased slightly along the study period. The indication to perform the test is not always clear, and patients detected with deficiency are not always referred to a specialist. Keywords: alpha-1 antitrypsin deficiency, population based, diagnosis, screening, COPD